2016
DOI: 10.1515/eletel-2016-0002
|View full text |Cite
|
Sign up to set email alerts
|

Noise Detection for Biosignals Using an Orthogonal Wavelet Packet Tree Denoising Algorithm

Abstract: Abstract-This article deals with the noise detection of discrete biosignals using an orthogonal wavelet packet. In specific, it compares the usefulness of Daubechies wavelets with different vanishing moments for the denoising and compression of the digitalised biosignals in case of surface electromyography (sEMG) signals. The work is based upon the discrete wavelet transform (DWT) version of wavelet package transform (WPT). A noise reducing algorithm is proposed to detect unavoidable noise in the acquired data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…They reported better results using the db4 at level 3. These results appear to be consistent with the literature, since most studies have reported using either the db2 [ 73 , 74 , 75 , 76 , 77 , 78 , 79 ] or the db4 [ 67 , 80 , 81 , 82 , 83 , 84 ]. In terms of the optimal decomposition level, level 4 appears to be the most widely used [ 5 , 19 , 71 , 77 , 82 , 85 , 86 ], while the level 3 is also frequently chosen [ 25 , 72 , 87 , 88 , 89 , 90 ].…”
Section: Contaminant Reduction Methodssupporting
confidence: 92%
“…They reported better results using the db4 at level 3. These results appear to be consistent with the literature, since most studies have reported using either the db2 [ 73 , 74 , 75 , 76 , 77 , 78 , 79 ] or the db4 [ 67 , 80 , 81 , 82 , 83 , 84 ]. In terms of the optimal decomposition level, level 4 appears to be the most widely used [ 5 , 19 , 71 , 77 , 82 , 85 , 86 ], while the level 3 is also frequently chosen [ 25 , 72 , 87 , 88 , 89 , 90 ].…”
Section: Contaminant Reduction Methodssupporting
confidence: 92%
“…They reported better results using the db4 at level 3. These results appear to be consistent with the literature, since most studies have reported using either the db2 [73][74][75][76][77][78][79] or the db4 [67,[80][81][82][83][84]. In terms of optimal decomposition level, level 4 appears to be the most widely used [5,19,71,77,82,85,86], while the level 3 is also frequently chosen [25,72,[87][88][89][90].…”
Section: Denoising Methods After Wavelet Decompositionsupporting
confidence: 87%
“…Unlike DWT, Wavelet Packet Transform (WPT) has the advantage of denoising on frequency bands of the same width. WPT denoising has been applied in various fields including speech enhancement [26], [27], noise detection in bio-signals [28] and atomic force microscopy image denoising [29]. WPT has proven to be particularly suitable for background denoising with a specific frequency content.…”
Section: Related Workmentioning
confidence: 99%
“…For simplicity, we keep using then the small architectures from Table I. Indeed, we also tried three architectures with number of parameters around n p = 8670: [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] with n p = 5488, [8-16-32] with n p = 6632 and with n p = 21216. The best performing is the with S p = 19.3 and S r = 19.5 for the first fold.…”
Section: B Choice Of the Nn Architectures: Airport Background Removalmentioning
confidence: 99%